2013
DOI: 10.4236/aasoci.2013.37038
|View full text |Cite
|
Sign up to set email alerts
|

Marital Name Changing: Delving Deeper into Women’s Reasons

Abstract: Using a mixed method approach, this study examines women's reasons for the traditional practice of marital name changing. We utilize data collected via a questionnaire administered to first-year college students at a southeastern US public university and data gathered from in-depth interviews with recent college graduates. The quantitative results show that the reasons given for marital name changing are closely tied to social norms. The results from the qualitative analyses reveal more specifically how social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Similar findings have been reported by other investigators (e.g., Hoffnung, 2006;Twenge, 1997). Others have reported that large majorities of unmarried college women also plan to change their names upon marriage (Keels & Powers, 2013).…”
Section: Last Names Of Adults In Same-sex and Other-sex Relationshipssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings have been reported by other investigators (e.g., Hoffnung, 2006;Twenge, 1997). Others have reported that large majorities of unmarried college women also plan to change their names upon marriage (Keels & Powers, 2013).…”
Section: Last Names Of Adults In Same-sex and Other-sex Relationshipssupporting
confidence: 89%
“…In patriarchal tradition, a woman takes her husbands' name upon marriage (Keels & Powers, 2013). Since all heterosexual couples in our sample were married, all had encountered this opportunity for women to consider changing their last names.…”
Section: Discussionmentioning
confidence: 99%
“…Rationales for women's marital surname change have been found in one U.S. survey to closely relate to social norms (Keels and Powers 2013). "(S)ociodemographic cleavages" such as left-or right-leaning politically have also been found to predict marital surname change in a U.S. study (Hamilton et al 2011, p. 149).…”
Section: Regional and Jurisdictional Variationmentioning
confidence: 95%